An User-Centered Evaluation of Two Socially Assistive Robots Integrated in a Retirement Home - Jerez Cordoncillo, Antonio; Iglesias, Ana; Pérez-Lorenzo, José Manuel; Tudela, Alberto; Cruces, Alejandro; Bandera-Rubio, Juan Pedro (Springer, 2024)
Socially assistive robots are receiving a growing interest in the health and social care sectors. They are considered a promising technology to add value to the work of caregivers, and relieve them of simple and repetitive tasks. However, these robots currently face significant difficulties when deployed in everyday scenarios due to a number of factors. Most of these factors are related to insufficient consideration of the user perspective and incorrect evaluation procedures. This paper aims to address these issues. Its objective is to analyze the long-term accessibility, usability, social acceptance and user experience for two different socially assistive robots performing the same tasks in a retirement home. The evaluation procedure is based on a framework specifically designed to consider these criteria. Collected results show that both robots received an overall positive feedback. Although the number of users participating in the evaluation was not very high, due to the chosen recruitment criteria and the period of activity of this research project, during the COVID19 pandemic, these results allow to extract relevant insights towards a meaningful use of social robots in shared social care contexts.
Keywords: Robótica; Tecnología; Asistencia social; Electrónica; Socially assistive robot (SAR); Long-term evaluation; User studies; Human–robot interaction (HRI)